Peran Valuta Asing Dan Hukum Internasional Dalam Mendukung Perdagangan Internasional - Hawari, Naufal; Nugraha, Rafi Surya; Aulia, Naswa Citra; Adi S, Muhammad Alfeon Putra; Ar Ramadhan, Chelsea Olivia Ayu; Fathurrahman, Adam Wildan; Setyawan, Edho (Fakultas Hukum Universitas Islam Batik Surakarta, 2025)
This research discusses the role of foreign exchange and international law in supporting international trade in this study using normative research methods. The main focus in this study is how foreign exchange contributes to smooth transactions between countries and how international law regulates mechanisms and protection in foreign exchange transactions between countries. The data is obtained through a literature study of scientific journals, legal articles, and documents relevant to this research. The results of the study discuss that foreign exchange has an important role as a medium of exchange in global trade, allowing countries to export and import efficiently. On the other hand, international law provides a normative foundation through exchange rate regulation, currency conversion, transaction transparency, and financial dispute resolution between countries. International institutions such as the International Monetary Fund (IMF), World Trade Organization (WTO), and Bank for International Settlements (BIS) play an important role in monitoring and enforcing these provisions. The synergy between the foreign exchange system and the rules of international law is the key to creating stability and legal certainty in international trade.